Limits to Ecological-based Planning in Zimbabwe. The Case of Harare - Muzenda, Archimedes; Chirisa, Innocent (TeMA - Journal of Land Use, Mobility and Environment, 2014)
This paper explores the feasibility of adopting ecological based planning in low-income residential development. It explicates that in developing countries efforts by housing authorities have been on housing provision irrespective of the environmental threats to sustainability. As these houses are built, future of urban ecology is under threat. The questions regarding this phenomenon are several: how do low-income populations perceive environmental issues of urban settlements? How capable and willing are the local authorities to embrace and apply ecological based planning in residential development? What are the facilitating instruments of ecological-based planning? What are the prospects of integrating ecological based planning to low-income residential development? What are the restraining factors towards embracement of ecological based planning and how best can they be harnessed towards future ecological cities? The case study of Hatcliffe residential area in Harare shows that there are many challenges to overcome uncoordinated planning approaches, ineffective policies and legislative frameworks, weak institutional settings, financial constraints, outdated planning standards and regulations, poverty, lack of environmental stewardship and lack of political will among others. The study findings call for robust environmental conservation strategies, strong environmental stewardship, responsive institutional and funding mechanism backed by realistic legislative frameworks and robust policy rectification.